Ways to Improve the Efficient Operation of Digital Banks in Uzbekistan (European Journal of Economics, Finance and Business Development, 2024)
The article focuses on digital banking, which is a new and fast-growing trend in banking. The article analyzes the ways of development of digital banking and transformation of banks, examines models of digital banking in developed countries and possible ways of their application in Uzbekistan.